The Role of Attitude and Purchase Impulse in Forming Online Repurchase Intention - Azka, Ravi Muhamad, Albari (Profesional Muda Cendekia Publishing, 2024)
Research Aims: E-commerce platforms are the fruit of rapid technological advances in the business sector. Building consumer trust and encouraging them to make purchases with several factors is a step taken by several E-commerce platforms so that consumers are interested and have repurchase intentions. This study attempts to reveal the factors underlying consumer repurchase intentions online on e-commerce through attitudes driven by perceived usefulness and external factors that drive purchases such as ease of use. Design/methodology/approach: This study will involve those who have the Shopee application and actively shop using the e-commerce. The number of samples was determined as many as 245 people, selected using the convenience sampling method. The research data obtained primarily, collected using a questionnaire, and will be analyzed using the SEM approach and the assistance of the SmartPLS data processing program. Research Findings: The results of the study show the role of attitude as a mediator variable of the positive influence of perceived usefulness and ease of use of e-commerce shopping sites on online repurchase intentions. The buying impulse also functions as a mediator variable of the positive influence of ease of use on the purchase intention. The results of the study also show that a person's attitude is more dominant in forming repurchase intentions than their buying impulse. Meanwhile, to form a buying attitude, the perceived usefulness of consumers has a more positive influence than ease of use. Theoretical Contribution/Originality: This research can add to the research discourse that reveals the dominance between attitude and buying impulse in influencing repurchase intention, as well as the strength of the influence between perceived usefulness and ease of use in shaping consumer buying attitudes. Keywords: Perceived Usefulness, Perceived Ease of Use, Buying Impulse, Attitude, Online Repurchase Intention